Utrata wartości aktywów finansowych - Więcław, Wojciech (The Depreciation of Financial Assets, 2005)
The paper presents main accounting problems related to estimation of impairment of financial assets. Rules of estimation of financial assets impairment result from the assumptions of measurement rules, appropriate to different categories of financial assets. Financial assets held to maturity and loans and receivables are measured by discounting expected cash flows at the original effective rate. In the case of financial assets available for sales and financial assets held for trading, impairment is estimated on the basis of fair value of financial asset. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 228-238